A questão agrária na formação territorial brasileira - uma perspectiva de caracterização estratégica - Sousa, Ronilson Barboza de (2020)
The coup that ousted Dilma Rousseff, from the Workers Party (PT), the presidency of the republic of Brazil, in 2016, prompted, among other issues, an assessment of the petist working class hegemony experience, and (re) placed, in the center of the debate, between leftist organizations and intellectuals, is the question of the strategy of the Brazilian revolution. We sought to contribute to this debate by analyzing the agrarian question - understood as an expression of a society-space relationship, how society relates and appropriates land, its control and production, and how it is put into issue in the actual movement of social classes. Thus, the objective of the present study was to analyze the agrarian issue in the Brazilian territorial formation from a strategic characterization perspective, communicating with the strategies of the Brazilian left, which hegemonized the working class, at different times. The analysis is oriented in the perspective of the method of historical and dialectical materialism and, therefore, in Marxist theory, by enabling the understanding of the essence of the capitalist mode of production, of the social problems generated by its dynamics, and pointing the way of its overcoming, of the overcoming class society. Hence, Marxism has a strategic theoretical dimension: the strategy of the communist (international) revolution. In this perspective, geography becomes fundamental, by understanding the dynamics of the capitalist production of space, the Brazilian territorial formation and, in this way, the agrarian question. On the other hand, the importance for geography comes from the fact that, despite the diversity and relevance of research on the agrarian question, there are not so many studies concerned with understanding it from a strategic characterization perspective. Many organizations and intellectuals also analyze Brazilian territorial formation through the supposed dualism of independent sectors, “backwardness” and “modernity”. Considered modern because it has traveled a capitalist path; and the backwardness one (although in some cases it does not explicitly use this word), where predominates the agrarian based economy, which delays their development and the modern sector. The conclusion of these analyzes is not to point directly to a socialist strategy and revolution. Democratic mediation is needed to achieve socialism only then. In the current configuration of the agrarian question in Brazil, there is an integration of capital from various sectors and origin (national and international): acquisitions, mergers and associations between capitals; In addition to the control of foreign companies over land in Brazil. There was an articulation of monopoly capital in large land ownership, known as agribusiness, which has caused structural changes with its expansion over the Brazilian countryside. The expansion of agribusiness, the combination of capital in the countryside, the capitalist exploitation of labor, cannot be considered a backward democratic task, as it is not only part of the way capitalism expands in the country, but also places itself directly in a socialist ground. However, beyond this reality, we have the use of land for speculation, reserve of value, subaltern integration of family farmers and peasants into the capital, indigenous peoples, quilombolas and peasants, who claim land and resources to produce food and ensure the reproduction of their way of life. All these questions are articulated, however, this last reality does not directly place the capital-labor contradiction and the socialization of labor, and therefore can be considered as democratic tasks and / or claims. Nevertheless, it also clashes with capital and its way of expanding in the countryside. From this perspective, we consider that the agrarian question in Brazil is a combination of a democratic and socialist task, which, by colliding with capital, points to the need for its overcoming.